Stratification and overturning circulation are intertwined controls on ocean heat uptake efficiency in climate models - L. Vogt; L. Vogt; J.-B. Sallée; C. de Lavergne (Ocean Science)
The global ocean takes up over 90 % of the excess heat added to the climate system due to anthropogenic emissions, thereby buffering climate change at Earth's surface. A key metric for quantifying the role of the oceanic processes removing this heat from the atmosphere and storing it in the ocean is the ocean heat uptake efficiency (OHUE), defined as the amount of ocean heat uptake per degree of global surface warming. Despite the importance of OHUE, there remain substantial uncertainties concerning the physical mechanisms controlling its magnitude in global climate model simulations: ocean mixed-layer depth, Atlantic Meridional Overturning Circulation (AMOC) strength, and upper-ocean stratification strength have all been previously proposed as controlling factors.